Simulação Monte Carlo da resposta de um monitor individual de nêutrons tipo albedo - Freitas, Bruno Mendes (2018)
For a proper evaluation of the occupational neutrons dose, using individual monitors, expensive, time-consuming and even unviable calibrations are required. The work intended to simulate and study the response of an albedo neutron dosimeter, aiming to contribute to a better performance in the evaluation of the occupational dose. The dosimeter was modeled using the MCNPX Monte Carlo code and the calculation of the HP(10) response was carried out for several standard and workplace neutron spectra. Different methodologies were applied to the calculate the TLD responses. The results obtained through simulation were compared with experimental results showing agreement better than 90%. The results obtained in workplace neutron spectra were classified and equations were adjusted for the calculate the dosimeter response using the incident and albedo reading ratio. Therefore, the simulation developed in this work provided a wide analysis of the response of IRD dosimeter in several spectra. In addition, the obtained data will aid in a better evaluation of the occupational dose with this dosimeter, filling an existing gap.